2017
DOI: 10.3892/mmr.2017.6407
|View full text |Cite
|
Sign up to set email alerts
|

Extravasated platelet aggregation in the livers of rats with drug-induced hepatic sinusoidal obstruction syndrome

Abstract: Abstract. Oxaliplatin-based chemotherapy plays an important role in the treatment of colorectal liver metastases. Oxaliplatin, however, causes sinusoidal obstruction syndrome (SOS), which is characterized by portal hypertension, splenomegaly, thrombocytopenia, and liver dysfunction. SOS is diagnosed histopathologically by disruption of the sinusoidal endothelium, collagen deposition, fibrosis especially around zone 3, dilatation of the sinusoidal space and congestion. This study assessed the characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 40 publications
4
21
0
Order By: Relevance
“…This created gaps allowing red blood cells to enter the space of Disse and deteriorate the sinusoidal lining, all of which embolized and reduced sinusoidal blood flow. 24 Embolization in the space of Disse was further confirmed in a recent study by Hirata et al (2017) 25 ( Table 2). In the two other studies, DeLeve et al found that the loss of sinusoidal integrity is directly related to an increase in matrix metalloproteinase-9 (MMP-9) activity, which is reinforced by a decrease in nitric oxide (NO) production.…”
Section: Characterization Of Sos Using Animal Modelssupporting
confidence: 65%
See 1 more Smart Citation
“…This created gaps allowing red blood cells to enter the space of Disse and deteriorate the sinusoidal lining, all of which embolized and reduced sinusoidal blood flow. 24 Embolization in the space of Disse was further confirmed in a recent study by Hirata et al (2017) 25 ( Table 2). In the two other studies, DeLeve et al found that the loss of sinusoidal integrity is directly related to an increase in matrix metalloproteinase-9 (MMP-9) activity, which is reinforced by a decrease in nitric oxide (NO) production.…”
Section: Characterization Of Sos Using Animal Modelssupporting
confidence: 65%
“…Even those that used other small rodents varied the dosage of MCT. 29,33 Moreover, after 2009, many studies using rats switched to 90 mg/kg doses, although still citing the original model by DeLeve et al 13,14,[25][26][27][28][34][35][36][37][38][39] However, as the first study to use this dosage, briefly summarize SOS development in their model in four phases over seven days-early toxicity on day 1, severe sinusoidal changes and coagulative necrosis on days 2-3, development of fibrosis on days 4-6, and almost complete recovery on day 7. 37 This four-phase course of SOS produced similar histopathological changes to human SOS (day 2) and matches the ten-day staging of the 160 mg/kg model proposed by DeLeve et al (Figure 1), a result that directly opposes the "dosage window" of 100-200 mg/kg.…”
Section: Comparison Of Methodologiesmentioning
confidence: 99%
“…A central pathological event under these conditions is a toxic destruction of hepatic sinusoidal endothelial cells, with sloughing and downstream occlusion of terminal hepatic venules. Extravasated platelet aggregation in the space of Disse (as observed in Mfsd1 KO and Glmp KO mice) was observed in a rat model for SOS (Hirata et al, 2017). Contributing factors are LSEC glutathione- and nitric oxide depletion.…”
Section: Discussionmentioning
confidence: 90%
“…CD34 is an intercellular adhesion protein often used to detect the presence of sinusoidal capillarization [ 47 50 ]. Previous reports revealed that CD34 expression occurred simultaneously with SEC injury, hepatocyte apoptosis, and liver functional impairment [ 47 , 49 , 50 ]. In our hepatic IRI model, sinusoidal capillarization occurred mainly in zone 3 and may have affected hepatic parenchymal injury, including vacuolization, necrosis, and apoptosis, which developed in zone 3 compared with zone 1.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism for this may be associated with reduced red blood cell velocity induced by deteriorated SEC function. Regarding the congestion at zone 3, we previously used a VOD model, characterized by severe congestion and SEC injury in zone 3, to demonstrate that extravasated platelet aggregation (EPA) occurred after sinusoidal endothelial denuding, and platelet activation resulted in the release of PAI-1 [ 49 , 50 ]. PAI-1 negatively regulates hepatocyte proliferation by inhibiting urokinase-type plasminogen activator, which activates hepatocyte growth factor [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%